THE INFLUENCE OF PRICE, SERVICE QUALITY, AND PHYSICAL ENVIRONMENT ON CUSTOMER SATISFACTION. CASE STUDY MARKOBAR CAFE MANDO - Cristo, Mandang; Saerang, David P. E; Worang, Frederik (Universitas Sam Ratulangi, 2017)
Abstract: The Customer Satisfaction is the extent to which the responds of products or service meet the expectation of buyers. If the performance of the product or service is higher than the expectation of customer, the buyers will be satisfied. There are several factors that influence customer satisfaction such as price, service quality and physical environment. At the beginning of 2016 Markobar café become famous, and now Markobar Café already open some new brach in several cities in Indonesia and also in Manado. This studied aimed to determine the effect of price, service quality and physical environment on customer satisfaction in Markobar Café Manado. The type of this research is Multiple Regression analysis and the data was collected from 60 respondents of Markobar Café’s Manado. This research showed that simultaneous price, service quality and physical environment significantly influence customer satisfaction. Partially service quality and physical environment significantly influence customer satisfaction and price variable is not significant influence on customer satisfaction. Service quality and physical environment has contributed greatly to the customer satisfaction so the manager should consider about that two factors.Keywords: price, service quality, physical environment, customer satisfaction.